Pembelajaran Bahasa Indonesia secara Daring pada Masa Pandemi Covid-19 - I Gede Nurjaya; I Nyoman Yasa (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The Covid-19 pandemic has forced Indonesian language lecturers to use internet-assisted technology. The worry arises because all lecturers have not mastered professional skills in using assisted internet technology, affecting the quality of Indonesian language learning, especially at the Ganesha University of Education. This qualitative research discusses (1) the learning tools used by Indonesian language lecturers and (2) the process of Indonesian learning during the Covid-19 Pandemic era. The subjects of this research are Indonesian language lecturers at the Ganesha University of Education. Data collection techniques were carried out using observation, open interviews, and documentation studies. The data analysis technique used the Milles and Huberman analysis model and the TPACK principle. The results showed that (1) Indonesian language learning during the Covid-19 pandemic era had been planned in advance through the preparation of learning tools; and (2) Indonesian lecturers were able to combine aspects of technology skills, pedagogy, and content knowledge in learning carried out both synchronously and asynchronously.